Aplikasi Remote Sensing dan Geographic Information System untuk Perencanaan Penggunaan Lahan Pertanian Berbasis Agroekosistem di Kota Denpasar - RIAN REHMAMANA; INDAYATI LANYA; I NYOMAN DIBIA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Remote Sensing and Geographic Information System Application forAgroecosystem Based Agricultural Land Planning in Denpasar City This study aims to determine the level of potential agroecosystem land suitability, compile databases, build information systems and create maps of land useplanning for food crops and horticulture based on remote sensing and GeographicInformation System (GIS). This research took place from September 2018 - December2018 using an exploratory method which included analysis of satellite imagery, fieldsurveys, analysis of field data and laboratory data, land suitability classification,mapping of land suitability classes, compiling data bases, building informationsystems, commodity zoning, planning land use, and mapping of land use planning.Potential land suitability classes for irrigated rice fields are generally very suitable inall of Denpasar City (41 subak) but additional fertilizer is needed, especially N.Potential land suitability classes for horticultural (vegetable and fruit) commodities areclassified as appropriate (S2) through drainage improvements and fertilization.Climate factors are generally very suitable (S1) for food crops, and suitable (S2) forhorticulture plants. The train factor is generally classified as very suitable (S1) in foodcrops and horticulture unless the drainage factor is relatively slow and nutrientavailability is classified as moderate.